DEGRADATION OF TETRACYCLINE BY FLOATING PHOTOCATALYST TiO2/Ni-COCONUT FIBER - Putri, Lavena Imelda; Agustiawan, Deri; Sugandi, Didiek; Arfida, Khaizurani; Mardhatilla; Wahyuni, Nelly (Universitas Airlangga, Campus C Mulyorejo, Surabaya, Indonesia, 2023)
The photocatalyst process involves light (photons) as an energy source and catalysts such as TiO2 to accelerate the reaction. Efforts are made to reduce the band gap energy of TiO2 by shifting the absorption towards visible light using metal cation doping, such as Ni2+, and they can float on the surface with coconut fiber. XRD characteristics with TiO2 diffractogram experienced a 2Î¸ shift as an indication that Ni has entered the TiO2 structure and seen some peaks decreased in intensity after being embedded with coconut fiber as an indication that TiO2/Ni has successfully attached to the fiber. The band gap energy on TiO2 is 3.21 eV with a wavelength of 386.5 nm in UV light. TiO2/Ni-coconut fiber experienced a shift in band gap energy to 3.09 eV with a wavelength of 400.9 nm, which is in visible light. This indicates that Ni has successfully entered the TiO2 structure. The TiO2/Ni catalyst embraced with coconut fiber has a higher degradation activity than the catalyst without an embrainer, with a percent degradation of 28.66% for 120 minutes of irradiation. This is influenced by the amount of light that can be absorbed during the photocatalysis process.